Cultivar Variation in Tomato Seed Coat Permeability Is an Important Determinant of Jasmonic Acid Elicited Defenses Against Western Flower Thrips - Mouden, Sanae; Kappers, Iris F.; Klinkhamer, Peter G. L.; Leiss, Kirsten A. (Frontiers in Plant Science, 2020)
Induction of defenses is one of the most widely accepted eco-friendly approaches for management of pests and diseases. Seeds are receptive to resistance-inducing chemicals and could offer broad-spectrum protection at the early stages of development. However, seed treatment with elicitors has previously been shown to differentially influence induced defense responses among cultivars and thus, could hamper commercial exploitation. In this context, the objective of the present study was to evaluate the genotype-dependent ability of jasmonic acid (JA) to induce resistance against western flower thrips (WFT) at the seed stage. We examined the variation in inducibility of resistance in eight commercial tomato cultivars. Causal factors accounting for discrepancies in JA-induced responses at the seed stage were phenotypically and biochemically evaluated. Seed receptivity to exogenous JA appeared to be cultivar dependent. Thrips associated silver damage was only reduced in JA seed-treated plants of cultivar Carousel. Enhancement of resistance, was not associated with activation of defense-related traits such as polyphenol oxidase activity (PPO), trichomes or volatiles. Sulfuric acid scarification, prior to JA seed incubation, significantly augmented the embryonic responsiveness to JA in cv. Moneymaker without an adverse effect on growth. Hence, these results support the hypothesis that seed coat permeability is a key factor for successfully inducing JA mediated thrips defenses. The outcome of our study is of translational value as it creates opportunities for the seed industry to perform pre-treatments on non-responsive cultivars as well as for tomato breeding programs to select for genetic traits that affect seed permeability.